The case of Dr Alan Nunn May, 1946 (pg. 1) (1946)
1946 1945-1960 "The case of Dr Alan Nunn May, 1946 (pg. 1)" [HFR0129], 1946 The Association of Scientific Workers protested the sentence of ten years imprisonment imposed on Dr Alan Nunn May, a British physicist working in Canada, for breaking the Official Secrets Act. In early 1945, Dr May had passed a report on atomic research and some radioactive uranium to a representative of the Soviet Union. In his defence, Dr May said he had thought it wrong for a major ally not to be informed of these developments. The Association, with the National Council of Civil Liberties, the London Trades Council and other union organisations campaigned to reduce the prison sentence and to lift wartime restrictions on the free communication on information in science. Dr May served six years of his sentence and died in 2003.